TBIO-24. USING MOLECULAR GUIDED THERAPY IN PEDIATRIC NEURO ONCOLOGY PATIENTS: THE SUCCESS AND BARRIERS. (4th December 2020) - Armstrong, Beth; Schmitt, Morgan; VonBergen, Jayne
Abstract: Remarkable advances have been made in pediatric brain tumor treatments, however many of these children suffer significant side effects from standard chemotherapy-based treatment. Recent advances in precision medicine offer great hope to pediatric patients in terms of improved therapeutic precision, safety, and efficacy. However, there are barriers to implementing precision medicine that are best approached from a multi-disciplinary perspective. The goals of the Riley Hospital for Children at Indiana University Health Precision Genomics Neuro Oncology program are to optimize the treatment of children by assessing children's cancers for actionable molecular targets and finding available, affordable therapies that treat those actionable targets. Children are referred to the Riley Precision Genomics Neuro Oncology program at the time of diagnosis or with relapse. Tumor tissue is tested for somatic and germline findings. Riley's Precision Genomics Neuro Oncology program has received 55 patient referrals. Of these 55 patients, 46 (84%) had molecular analysis completed, and the results of 40 (87%) patients indicated actionable targets. Of the 40 patients with results, 23 (58%) patients went on to receive genomics guided therapy. Limited availability of tissue has accounted for 6 (13%) patients' lack of results. Many guided therapy options are oral medications, which positively impact patient's quality of life. The learner will increase their knowledge of how molecular guided therapy is now innovatively being used to treat children with cancer, and the challenges involved.